2001
DOI: 10.1128/jb.183.18.5213-5222.2001
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the MexEF-OprN Multidrug Efflux System Affects Cell-to-Cell Signaling in Pseudomonas aeruginosa

Abstract: Intrinsic and acquired antibiotic resistance of the nosocomial pathogen Pseudomonas aeruginosa is mediated mainly by the expression of several efflux pumps of broad substrate specificity. Here we report that nfxC type mutants, overexpressing the MexEF-OprN efflux system, produce lower levels of extracellular virulence factors than the susceptible wild type. These include pyocyanin, elastase, and rhamnolipids, three factors controlled by the las and rhl quorum-sensing systems of P. aeruginosa. In agreement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
266
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(286 citation statements)
references
References 54 publications
(43 reference statements)
18
266
0
2
Order By: Relevance
“…Mutants of the nfxC type have been isolated in the clinic, but they are not very common. The most likely explanation for this is their reduced virulence (102,109,111), together with the fact that these mutations appear to be less effective at engendering antibiotic resistance in vivo than they are under laboratory conditions (77).…”
Section: Mutational Resistance Related To Efflux Pumpsmentioning
confidence: 99%
“…Mutants of the nfxC type have been isolated in the clinic, but they are not very common. The most likely explanation for this is their reduced virulence (102,109,111), together with the fact that these mutations appear to be less effective at engendering antibiotic resistance in vivo than they are under laboratory conditions (77).…”
Section: Mutational Resistance Related To Efflux Pumpsmentioning
confidence: 99%
“…It has been suggested that the natural function of RND pumps might also include efflux of signal molecules required for cell-to-cell signaling (quorum sensing) [103]. Pseudomonas aeruginosa secretes a quinolone, designated PQS (Pseudomonas quinolone signal), which acts as quorum-sensing signal [95] and overexpression of MexEF-OprN was shown to affect PQS signalling [49]. This is a very interesting finding as quinolones constitute a widely used group of antimicrobials and are substrates for RND pumps.…”
Section: Natural Functions Of Rnd Efflux Pumpsmentioning
confidence: 99%
“…Short chain AHLs ͑ϽC8͒ are believed to be able to freely diffuse across the cell envelope; whereas AHLs with longer acyl side chains may depend on transport systems (Kohler et al, 2001). Several LuxI family proteins have been studied at the biochemical and structural level revealing their precise mode of action (Pappas et al, 2004).…”
mentioning
confidence: 99%